2011
DOI: 10.1097/ccm.0b013e3182120b56
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications in out-of-hospital cardiac arrest patients in the therapeutic hypothermia era*

Abstract: Infectious complications are frequent after cardiac arrest and may be even more frequent after therapeutic hypothermia. Despite increase in care costs, long-term and clinically relevant outcomes do not seem to be impaired. This should not discourage the use of therapeutic hypothermia in cardiac arrest survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
4
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 38 publications
3
100
4
12
Order By: Relevance
“…9 Some publications, including meta-analyses, did not find any increased risks using TH, 5,36,37 but other authors observed a higher incidence of infections with cooling, mainly pneumonia. 17,[38][39][40] In the present study, minor side effects were observed more frequently with invasive cooling and were dominated by minor bleedings and venous catheter bacterial colonization without septic shock occurrence. The systematic microbiological cultures of all venous catheters and the higher number of venous accesses used in the endovascular group may have contributed to this result (Table VI in the online-only Data Supplement).…”
Section: Side Effectsmentioning
confidence: 99%
“…9 Some publications, including meta-analyses, did not find any increased risks using TH, 5,36,37 but other authors observed a higher incidence of infections with cooling, mainly pneumonia. 17,[38][39][40] In the present study, minor side effects were observed more frequently with invasive cooling and were dominated by minor bleedings and venous catheter bacterial colonization without septic shock occurrence. The systematic microbiological cultures of all venous catheters and the higher number of venous accesses used in the endovascular group may have contributed to this result (Table VI in the online-only Data Supplement).…”
Section: Side Effectsmentioning
confidence: 99%
“…Evidence from stroke and TBI patients treated with TTM report increased incidence of pneumonia with TTM times exceeding 48-72 h [197,218] . Recent retrospective review of 421 patients from a single center demonstrated 67% of patients developed 373 infectious complications [219] . These were most commonly pneumonia (85%), bloodstream infections (9%), and catheter-related infections (3%).…”
Section: Logistics Of Deliverymentioning
confidence: 99%
“…(15,16) Owing to the active cooling process, recognition of fever is not possible. Pneumonia and sepsis have been found to be increased during hypothermia.…”
Section: Infectionsmentioning
confidence: 99%